Comparative study of efficacy of 30% Salicylic acid peel VsLong-pulsed 1064 nm Nd:YAG laser for treatment of Keratosis Pilaris - Zonunsanga (Our Dermatology Online, 2015)
Introduction: Keratosis pilaris(KP) is a disorder of keratinization of hair follicles characterized by keratin plugs in the hair follicles with perifollicular erythema. It may be inherited with X-Linked Dominant, or may be sporadic. Aim of the study: to compare the efficacy of 30% Salicylic acid and Long pulsed 1064nm Nd:YAG laser for treatment of keratosis pilaris. Materials and Methods: Out of 20 patients, 10 patients were given 30% Salicylic acid peel (after washing their face) every 15 days for 2 months. Another 15 patients were given the 1064 nm Nd:YAG Long pulse, Spot size: 10 mm, Pulse width: 30 ms every 4-6 weeks for 4 sitting. Results: Among salicylic acid treated group, only 2 out of 10 showed improvement between 50-75%, and were slightly satisfied; none showed >75% improvement, and 8 out of 10 failed to show >50% improvement and were considered as failure of the therapy. Among the Nd:YAG treated group, 3 out of 10 showed 50-75% improvement and were slightly satisfied;none showed > 75% improvement, 7 out 10 failed to show successful results i.e. >50% improvement. Conclusion: Both of the treatments are not much effective and do not give consistent and satisfactory results for treatment of keratosis pilaris.